(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Comminuted radial head fractures (Mason type III and IV) are frequently associated with elbow instability and poor outcomes when treated with excision or open reduction and internal fixation. Radial head arthroplasty has emerged as a preferred option for irreparable fractures, aiming to restore elbow stability, motion, and function. Objective: To evaluate the clinical, functional, and radiological outcomes of radial head prosthesis in the surgical management of comminuted radial head fractures from a surgical perspective. Methods: This prospective observational study was conducted at the Department of Orthopaedics, Comilla Medical College Hospital, from January 2023 to July 2025. Twenty-six adult patients with Mason type III or IV radial head fractures underwent primary radial head arthroplasty and were followed for a minimum of 12 months. Functional outcomes were assessed using the Mayo Elbow Performance Score (MEPS) and Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire. Pain was evaluated using the Visual Analog Scale (VAS), while elbow and forearm range of motion were measured with a goniometer. Radiological assessment focused on prosthesis position, joint congruity, and complications. Data were analysed using SPSS with statistical significance set at p < 0.05. Results: The mean age was 41.8 ± 11.2 years, with males comprising 69.2% of patients. At 12 months, mean elbow flexion was 130° ± 10°, with a mean flexion–extension arc of 120° ± 12°. Mean VAS scores improved significantly from 7.8 ± 1.0 preoperatively to 1.5 ± 0.9 (p < 0.001). The mean MEPS was 88.6 ± 9.1, with 84.6% of patients achieving excellent or good outcomes. The mean DASH score improved to 14.2 ± 7.5 (p < 0.001). Radiological outcomes were satisfactory in all cases, with no prosthesis loosening or revision surgery required. Conclusion: Radial head arthroplasty provides reliable pain relief, restoration of functional motion, and favourable short-term outcomes in comminuted radial head fractures when performed early and combined with appropriate soft-tissue management and rehabilitation. J Com Med Col Teachers’ Asso Jan 2026; 30(1): 53-62